Post-Traumatic Stress Disorder and School Performance Among Adolescents Students in Baghdad (Iraqi Journal of Medical Sciences, 2021)
Background: Post-traumatic stress disorder (PTSD) before adulthood has long-lasting effects on school performance among students, thus, early recognition and treatment are vital.Objective: To identify the effect of war trauma among secondary school students, test the rate of PTSD among students, and investigate the relationship between exposure to war trauma and effect on school performance.Methods: Total 108 (third intermediate class) students of both sex at two secondary schools. They screened by modified war trauma Questionnaire scale (CRIES-13) to diagnose PTSD and used impact on school performance scale.Results: The percentage of students who had >11 and above traumatic events during the preceding seven years was 38.9%. PTSD rate is 27.8% (above the cutoff point of 17 on children revised impact of events scale-13). PTSD rate is higher in females (63.3%) than 36.7% of males. The rate of impact on school performance is 43.5% (above the cutoff point of 21). The rate of impact on school performance is 83.3% among students with PTSD.Conclusion: The exposure to war trauma increases risk of PTSD among school children, number of traumatic events are high among adolescents, rate of PTSD is high in relation to events and higher in females than male and effect on school performance is high among students with PTSD.Keywords: Children, PTSD, school performanceCitation: Hussein HS, Jaber OA, Alwan YS. Post-traumatic stress disorder and school performance among adolescents' students in Baghdad. Iraqi JMS. 2021; 19(1): 72-81. doi: 10.22578/IJMS.19.1.10